TEMPERATURE DEPENDENCE OF OXYGEN ISOTOPE FRACTIONATION OF CO2 FROM MAGNESITE-PHOSPHORIC ACID REACTION - Sharma S.D.; Patil D.J.; Gopalan K. (My University, 2002)
New experimental results are reported on oxygen isotope fractionation factors, αT, between the δ18O compositions of carbon dioxide liberated by phosphoric acid in the temperature interval of 323 to 373K and that of total oxygen from a natural magnesite (MgCO3). These results are distinctly different from some previously published mutually inconsistent data, and can be expressed as a linear relationship: 103 lnαT = [{(6.845 +/- 0.475)*105}/T2] + (4.22 +/- 0.08), where 103 lnαT refers to fractionation at different temperatures T in Kelvin.Fractionation factors have also been determined at 323 and 368K on a natural calcite. The results on calcite are in excellent agreement with previously published data and can be written as:103 lnαT = [{(5.608 +/- 0.151)*105}/T2] + (3.89 +/- 0.08).The combined results on magnesite and calcite yield a computed value of α = 1.01117 for dolomite at 298K, assuming equal proportion of 0.5 mole of magnesium and calcium in dolomite, the previously reported experimental values being 1.01109 and 1.01110.